ANALISIS NILAI PROFIL PELAJAR PANCASILA DALAM MEMBENTUK KARAKTER KOMUNIKATIF SISWA - Rizqiyatul ‘Izzah Zulfiyah; Dina Pratiwi Dwi Santi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the independent curriculum is the Pancasila Student Profile which consists of five dimensions, one of them is the dimension of mutual cooperation. In relation to the dimension of mutual cooperation, communicative character is the key to this dimension. The communicative character that is built in schools is still limited to learning in the classroom only. This study aims to determine the form of student activities that reflect the values ​​of the Pancasila student profile that can form a communicative character. The method used is descriptive qualitative. Using data collection techniques through observation, interviews, and documentation. The sampling technique uses purposive sampling with certain considerations, the data that has been taken is primary data and secondary data. The data analysis technique uses the Miles and Huberman model in the form of data reduction, presenting data, and making conclusions. Using data validity tests that include credibility, transferability, dependability, and confirmability tests. The results of this study indicate that there are five student activities that reflect the values ​​of the Pancasila student profile in forming a communicative character, namely AKBARSAMAWA, group discussions, class pickets, congregational prayers, and scouts.